2020
DOI: 10.1146/annurev-nutr-122319-034601
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction and Aging in Humans

Abstract: Calorie restriction (CR), the reduction of dietary intake below energy requirements while maintaining optimal nutrition, is the only known nutritional intervention with the potential to attenuate aging. Evidence from observational, preclinical, and clinical trials suggests the ability to increase life span by 1–5 years with an improvement in health span and quality of life lived. CR moderates intrinsic processes of aging through cellular and metabolic adaptations and reducing risk for the development of many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 149 publications
0
80
1
5
Order By: Relevance
“…Dietary polyphenols likely act on human health through several mechanisms; it has been demonstrated that some polyphenols and their metabolites exert anti-atherosclerotic effects, improve endothelial function and antioxidant status, increase nitric oxide release, and modulate inflammation and lipid metabolism [ 5 , 26 , 31 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary polyphenols likely act on human health through several mechanisms; it has been demonstrated that some polyphenols and their metabolites exert anti-atherosclerotic effects, improve endothelial function and antioxidant status, increase nitric oxide release, and modulate inflammation and lipid metabolism [ 5 , 26 , 31 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, as mentioned in the column "Cognitively stimulating activities" (Supplementary table), education [3,10], occupational status [142,189], premorbid IQ estimation, and engagement in stimulating physical [140,148], intellectual, and leisure activities [83,178,201], as well as a balanced diet and nutrition [54,56,57], might all have a neuroprotective role in aging. The wide concept of "activity" includes both social interactions with one or more people and more solitary activities such as reading or gardening [124].…”
Section: Aging-modulatory Reserve Factors (Amf)mentioning
confidence: 99%
“…Regular physical activity protects against decline in locomotory function, and can reduce frailty (World Health Organization, 2015 ). Caloric restriction has been shown to considerably slow the onset of age-related disease, contributing to the compression of morbidity and senescence (Flanagan et al, 2020 ; Fontana & Klein, 2007 ). Numerous studies underway are searching for effective strategies to boost cognition (Blasimme, 2020a ; National Academies of Sciences, 2017 ).…”
Section: Ageing As a Plastic Phenotypementioning
confidence: 99%